Digital Ecosystems as the Key Driver of Post-Industrial Economic Development - Abdurasulova Dinara Abdubakiyevna (Uzbekistan Open Conference, 2025)
The article examines the role of digital ecosystems in the post-industrial economy, where knowledge and innovation are the main drivers of growth. It discusses the theoretical foundations of post-industrial development and analyzes the mechanisms of digitalization, artificial intelligence, big data, and platform-based business models. Special attention is paid to international aspects of digital competitiveness, labor market transformation, and human capital development. The challenges of digital transformation, including cybersecurity risks, social inequality, and ethical issues, are also considered.
Keywords: Post-industrial economy; digital ecosystem; innovation; digitalization; sustainable development